From the field to the assembly hall: the history of the kidney health resolution (2025)
Key events and a trajectory spanning more than 3 decades that led to the adoption of the World Health Organization resolution on kidney health, a historic milestone for public health, are described, highlighting the pioneering contributions of leaders from Latin America. Milestones include defining the concept of kidney health, framing chronic kidney disease within social determinants, pioneering programs, strategic alliances, and regional policies. Key events are contextualized, including the Puerto Rico Declaration, the Antigua Guatemala Summit, the El Salvador meeting on Mesoamerican endemic nephropathy, and the inclusion of chronic kidney disease medicines into the Pan American Health Organization Strategic Fund. The history of the World Health Organization resolution on kidney health shows how Latin America transformed an overlooked issue into a global political priority, demonstrating how science, cooperation, and a vision of equity have elevated a regional concern into a worldwide commitment. Today, the challenge is to implement this resolution to realize kidney health for all.